Prevalence and Risk Factors for New-Onset Hypertension in Labor - Ankumah, Nana-Ama E.; Alrais, Mesk A.; Amro, Farah H.; Wiley, Rachel L.; Sibai, Baha M. (American Journal of Perinatology, 2020)
Objective Little is known about prevalence, risk factors, rate of treatment, or adverse outcomes associated with intrapartum hypertension. Thus, our objective was to describe these findings.Study Design This was a retrospective study of laboring term gestations with no history of hypertensive disorders. Intrapartum blood pressures were reviewed, and women were subdivided based on blood pressures: normal (<140 mm Hg systolic and <90 mm Hg diastolic), mild hypertension (140–159 or 90–109), and severe hypertension (≥ 160 or ≥ 110). Groups were compared using chi-square test and analysis of variance.Results A total of 724 women were studied during 4 months: 248 (34%) had mild and 69 (10%) had severe hypertension. Severe hypertensives were more likely to be nulliparous, obese, or have received an epidural or oxytocin. There were no cases of eclampsia, stroke, or pulmonary edema in severe hypertensives (95% confidence interval, 0–5). Despite severely elevated pressures, only 4/69 (6%) patients received intravenous antihypertensive therapy, and 3 (4%) required medications at discharge.Conclusion One in 3 women exhibits mild hypertension and 1 in 10 develop severe hypertension in labor. Only 6% of patients received treatment for severe blood pressures. This study highlights lack of treatment of hypertension in labor and further investigation into causes and outcomes of intrapartum elevations of blood pressures.
Keywords: hypertension; labor; nulliparity; obesity